The Automatic Evaluation of Regularity and Semantic Decodability in Wallpaper Decorative Patterns. (August 2019) - Fu, Kaili; Zhang, Yilei; Lin, Xun
The perception and evaluation of decorative patterns can have a high impact in daily life but has received little empirical attention. This article attempts to offer some insight in terms of the regularity and semantic decodability. The implicit attitudes of subjects were measured by the Implicit Association Test. The results showed that regularity and semantic information can be automatically evaluated. The regular and realistic wallpaper decorative patterns are implicitly preferred to random and abstract ones. The Implicit Association Test effect of the former was greater than the latter. The increase in the number of motifs led to a decrease in the response latencies of regular and realistic patterns. The findings indicated that the processing fluency of wallpaper patterns is enhanced by a translational symmetry operation and a higher conceptual fluency of motifs. The resulting processing acceleration in high-density patterns may be due to the formation of a better Gestalt when the motifs are closer to one another.